2022
DOI: 10.1111/ijfs.16065
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of curcumin‐mediated photodynamic technology (PDT) on polycyclic aromatic hydrocarbons in oysters and toxicity evaluation of PDT‐treated oysters

Abstract: Summary This study investigated the degradation effect of curcumin‐mediated photodynamic technology (PDT) on polycyclic aromatic hydrocarbons (PAHs) in oysters, and evaluated the safety of PDT‐treated oysters through acute and subacute toxicity experiments. The results demonstrated that curcumin‐mediated PDT could effectively degrade multi‐component PAHs in oysters, the maximum removal efficiency could reach 80.20% (10 μmol L−1 curcumin concentration and 54 J cm−2 light energy density). Acute toxicity experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…While only a few studies have examined this association in animal models or case studies with small sample sizes, our findings offer valuable insights. Zhi et al (2022) observed no significant impact of PAH-treated oysters on rat RDW-CV 33 , while Booker & White (2005) reported a dose–response relationship between Benzo(a)pyrene (BaP) and RDW in mice exposed to varying concentrations of BaP 34 . In a study of 53 petrochemical plant workers, Wang et al (2015) found significant non-parametric Spearman correlations between urinary 1-OHP concentration and red cell indices MCH and RDW 35 .…”
Section: Discussionmentioning
confidence: 99%
“…While only a few studies have examined this association in animal models or case studies with small sample sizes, our findings offer valuable insights. Zhi et al (2022) observed no significant impact of PAH-treated oysters on rat RDW-CV 33 , while Booker & White (2005) reported a dose–response relationship between Benzo(a)pyrene (BaP) and RDW in mice exposed to varying concentrations of BaP 34 . In a study of 53 petrochemical plant workers, Wang et al (2015) found significant non-parametric Spearman correlations between urinary 1-OHP concentration and red cell indices MCH and RDW 35 .…”
Section: Discussionmentioning
confidence: 99%